Publisher Correction: A lightweight neural network with multiscale feature enhancement for liver CT segmentation - Mohammed Yusuf Ansari (16904523) (2022)
Correction to: A lightweight neural network with multiscale feature enhancement for liver CT segmentation: https://dx.doi.org/10.1038/s41598-022-16828-6, published online 19 August 2022. The original version of this Article contained errors in References 1 and 2, which were incorrectly given as: 1.Dakua, S. P. journaltitlePerformance divergence with data discrepancy: A review. Artif. Intell. Rev., 40, 429–455. https://doi.org/10.1007/s10462-011-9289-8 (2013). 2.Dakua, S. P. journaltitleTowards left ventricle segmentation from magnetic resonance images. IEEE Sens. J., 17, 5971–5981. https://doi.org/10.1109/JSEN.2017.2736641 (2017). The original Article has been corrected. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-022-20472-5